Effects of radio- and microwaves emitted by wireless communication devices on the functions of the nervous system selected elements - Piotr Politański; Alicja Bortkiewicz; Marek Zmyślony (Nofer Institute of Occupational Medicine, 2016)
Nervous system is the most "electric" system in the human body. The research of the effects of electromagnetic fields (EMFs) of different frequencies on its functioning have been carried out for years. This paper presents the results of the scientific literature review on the EMF influence on the functioning of the human nervous system with a particular emphasis on the recent studies of the modern wireless communication and data transmission systems. In the majority of the analyzed areas the published research results do not show EMF effects on the nervous system, except for the influence of GSM telephony signal on resting EEG and EEG during patients' sleep and the influence of radiofrequency EMF on the cardiovascular regulation. In other analyzed areas (EMF impact on sleep, the evoked potentials and cognitive processes), there are no consistent results supporting any influence of electromagnetic fields. Neurophysiological studies of the effect of radio- and microwaves on the brain functions in humans are still considered inconclusive. This is among others due to, different exposure conditions, a large number of variables tested, deficiencies in repeatability of research and statistical uncertainties. However, methodological guidelines are already available giving a chance of unifying research that definitely needs to be continued in order to identify biophysical mechanisms of interaction between EMFs and the nervous system. One of the EMF research aspects, on which more and more attention is paid, are inter-individual differences. Med Pr 2016;67(3):411-421